2013
DOI: 10.1177/030089161309900408
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Two-Dimensional Radiotherapy of Pancreatic Carcinoma: A Feasibility Study

Abstract: The clinical benefits of radiotherapy in pancreatic tumors should not be withheld from patients treated in centers only with two-dimensional technology. Prospective trials, particularly in developing countries, would be useful to evaluate the efficacy in this setting of involved-field two-dimensional treatments using the dose and fractionation defined in this analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a previous study, we observed that with 2D-SRT, it is possible to meet the current standard dose-volume constraints ( 7 ) only by using lower total doses (30–36 Gy) ( 11 ). In a subsequent study, we defined the optimal fields size for involved-field irradiation of CaP with 2D-SRT technique ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we observed that with 2D-SRT, it is possible to meet the current standard dose-volume constraints ( 7 ) only by using lower total doses (30–36 Gy) ( 11 ). In a subsequent study, we defined the optimal fields size for involved-field irradiation of CaP with 2D-SRT technique ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we aimed at providing convenient 2D PCa target delineation tools. In the last years, our team worked on the optimization of 2D-RT in palliative treatments (33)(34)(35). Worth noting is that 2D-RT is still in use in several centers in the world.…”
Section: Treatment Machine ------------------------------------------mentioning
confidence: 99%